Lactate-to-albumin ratio index correlates with the occurrence and prognosis of acute kidney injury complicated by cardiac surgery - Congying Wang; Xin Sun; Kun Chen; Yaqing Shi; Lili Wang; Shuxia Chen; Dehua Li; Jian Gu (International Journal of Cardiology: Heart & Vasculature)
Background: The lactate-to-albumin ratio (LAR) is a novel biomarker associated with poor prognosis in critical illnesses. However, its relationship with cardiac surgery associated acute kidney injury (AKI) and prognosis remains unclear. This study aimed to investigate this relationship using data from the MIMIC database. Methods: A retrospective cohort study was conducted on 11,624 adult cardiac surgery patients admitted to the ICU. Logistic regression, restricted cubic spline (RCS) analysis, and subgroup analysis were used to assess the predictive value of LAR for AKI occurrence and adverse outcomes. Results: Of the 11,624 patients, 5,965 developed AKI. While LAR concentrations were higher in AKI patients, this association did not persist after multivariate adjustment for potential confounder. Logistic regression showed that LAR was independently associated with in-hospital and ICU mortality, even after adjusting for potential confounders. RCS analysis revealed a non-linear relationship between elevated LAR and increased mortality risk in AKI patients. Correlation analyses demonstrated that LAR was associated with longer hospital and ICU stays and higher SOFA scores. Subgroup analyses consistently showed that elevated LAR was associated with increased mortality risk in older adults, females, and patients with or without hypertension, chronic kidney disease, diabetes, or chronic heart failure. Conclusions: Among patients with acute kidney injury related to cardiac surgery, especially in those undergoing valve surgery, elevated LAR levels are associated with an increased risk of death, but not with the occurrence of acute kidney injury. Further validation is needed to confirm its predictive role.